IMPROVING READING ABILITY USING STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) AT THE 8TH YEAR OF SMP N 3 COLOMADU IN 2010/2011 ACADEMIC YEAR (AN ACTION RESEARCH) - FEBRIANA, FRIDA (2011)
This study is aimed at describing the implementation of teaching reading by using STAD and to know the students' achievement of the students' reading ability on STAD in learning reading. The result of this study is intended to give contribution to the teaching learning English of reading. The research was done to the eight year of SMP N 3 Colomadu, especially class VIIIF. The writer took 35 students as the subject of the research. The object of the research was the students' answer on written in the form of quiz, observation sheet, and questionnaires. Evidently, to find the significant difference between students' achievement before and after the action, the writer used paired t-test. The result showed that the t-observation is greater than the t-table; in degree of freedom N - 1 = 34 and level of significance 0,05. It means that there is a significant difference of the students' achievement before and after the implementation of STAD. The conclusion is the teaching reading using STAD to the eight year students of SMP N 3 Colomadu yields a good result. The result of the study shows that STAD improves and maintains teaching learning process of reading. STAD is an appropriate method in increasing the students' reading ability and helpful in teaching-learning process.